2021
DOI: 10.3390/nu14010022
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Foods Decrease Liver and Brain Alterations Induced by a High-Fat-Sucrose Diet through Restoration of Gut Microbiota and Antioxidant Enzymes

Abstract: Obesity is associated with cognitive deficit and liver alterations; however, it remains unclear whether a combination of functional foods could reverse cognitive damage and to what extent it would be associated with changes in gut microbiota and liver. With this aim, male Wistar rats were fed a high-fat-5%sucrose diet (HFS) for 4 mo. And were then fed for 1 mo. with bioactive foods. At the end of this period, liver, serum, feces, intestine, and brain samples were taken. Body composition, energy expenditure, LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…Gut microbiota has been characterized to have related underlying mechanisms in obesity for it plays a key role in energy homeostasis, immunity, and blood circulation ( 29 31 ). More and more evidence proved that compounds with high biological activity, such as polyphenols, can help modulate the gut microbiota dysbiosis and intervene the obesity ( 32 34 ). Chemical analysis showed that matcha supplied in this study was rich in EGCG, an antioxidant with high biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota has been characterized to have related underlying mechanisms in obesity for it plays a key role in energy homeostasis, immunity, and blood circulation ( 29 31 ). More and more evidence proved that compounds with high biological activity, such as polyphenols, can help modulate the gut microbiota dysbiosis and intervene the obesity ( 32 34 ). Chemical analysis showed that matcha supplied in this study was rich in EGCG, an antioxidant with high biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies about obesity-induced cognitive deficits have focused on the gut-brain axis, suggesting that microbiota dysbiosis is the primary response of the organism to hypercaloric diets, followed by neuroinflammation. In this regard, rats chronically fed with highfat-sucrose diet develop gut microbiota dysbiosis and concomitant accumulation of amoeboid microglia in the prefrontal cortex [192]. Likewise, a time-course study on rats fed with high-fat-sucrose diet showed a diet-induced progressive remodeling of microbiota leading to microbiota dysbiosis, accompanied by increased Iba1 expression in the nucleus tractus solitarius as early as 4 weeks on the diet, and exacerbated at 26 weeks [193].…”
Section: High-fat Diet-induced Metabolic Diseasementioning
confidence: 99%
“…Other mechanisms are also compromised in WD-induced cognitive damage: insulin (INS) signaling in the brain [ 60 , 68 ], blood-brain barrier (BBB) permeability [ 41 , 57 , 62 ], HPC inflammation [ 45 , 46 , 49 , 54 , 60 , 68 ], microglia activation [ 54 , 57 , 65 , 68 , 72 ], endoplasmic reticulum (ER) and oxidative stress [ 43 , 51 , 58 , 60 , 61 , 71 ], gut microbiome composition [ 44 , 46 , 54 , 56 , 58 ], and neurogenesis [ 59 ]. Therapeutic strategies based on modulating these mechanisms have demonstrated unequal effects on memory loss.…”
Section: Western Dietmentioning
confidence: 99%